Chinese institutions should be more proactive and transparent in promoting research integrity: A perspective - Zhang, Haihong (Frontiers in Research Metrics and Analytics, 2022)
China has significantly endeavored to promote research integrity. Institutions, which have been identified as the primarily responsible entity, face challenges and concerns of compliance, quality, and low efficiency. In this perspective, the problems and root causes of these challenging concerns are clarified from the Chinese viewpoint. In conclusion, the opinion that institutions should be more proactive and transparent in promoting research integrity is discussed. A practical suggestion is proposed, including team building, policy innovation, capacity building, researcher empowerment, and experience sharing.